15(6c-3)=9c-7

Simple and best practice solution for 15(6c-3)=9c-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15(6c-3)=9c-7 equation:


Simplifying
15(6c + -3) = 9c + -7

Reorder the terms:
15(-3 + 6c) = 9c + -7
(-3 * 15 + 6c * 15) = 9c + -7
(-45 + 90c) = 9c + -7

Reorder the terms:
-45 + 90c = -7 + 9c

Solving
-45 + 90c = -7 + 9c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-9c' to each side of the equation.
-45 + 90c + -9c = -7 + 9c + -9c

Combine like terms: 90c + -9c = 81c
-45 + 81c = -7 + 9c + -9c

Combine like terms: 9c + -9c = 0
-45 + 81c = -7 + 0
-45 + 81c = -7

Add '45' to each side of the equation.
-45 + 45 + 81c = -7 + 45

Combine like terms: -45 + 45 = 0
0 + 81c = -7 + 45
81c = -7 + 45

Combine like terms: -7 + 45 = 38
81c = 38

Divide each side by '81'.
c = 0.4691358025

Simplifying
c = 0.4691358025

See similar equations:

| 14x+-25=12x+85 | | 5x^2+6x+5y^2-y-9=0 | | -7=-(n-10) | | 10y=4y+7+5y | | 5(1+k)=-6(3-2k)+2 | | 10y=4y+5y | | 8v^2-74v-60=0 | | 2x^3+3x^2=5x | | -6(x+1)=4x-9+2(2x-5) | | 9v^2-62v-80=0 | | o=10y-40 | | 9n-2=7n-50 | | -9(x-1)+4x=-4 | | 6+2(5u-2)=-3(2u-3)+2u | | 2p+7p-4=50 | | -3(4n+8)+8=-14-12n | | 16+2=14 | | 7x+3(x-10)=90 | | 5(2x-10)=40 | | 3x=200 | | 7.3(5.1-x)+2.73=2x+2.8 | | 3x+12=10x+40 | | 3x^4-2x^3+6x^2=0 | | j-3=-3 | | 6x+2(3x-16)=40 | | 12-4m=0 | | -6+(m+8)=-11 | | 7m+38=4(m+5) | | 2x^3-24x+13=0 | | 4x+3(2x-17)=49 | | 5x^5+x+5=0 | | 6x^2+14x+30=0 |

Equations solver categories